2001
DOI: 10.3354/dao045033
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to a recombinant capsid protein of striped jack nervous necrosis virus (SJNNV) in turbot Scophthalmus maximus and Atlantic halibut Hippoglossus hippoglossus, and evaluation of a vaccine against SJNNV

Abstract: Immunisation by intraperitoneal injection of an oil-emulgated recombinant partial capsid protein (rT2) from striped jack nervous necrosis virus (SJNNV) was performed on adult turbot Scophthalmus maximus and Atlantic halibut Hippoglossus hippoglossus. A specific humoral immune response was recorded in both species, and the levels of rT2-specific antibodies increased markedly in all groups during the 20 wk experiment. A challenge model for SJNNV was established by intramuscular injection of juvenile turbot. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 29 publications
(41 reference statements)
1
48
1
3
Order By: Relevance
“…Intramuscular injection of the recombinant RGNNV coat protein, which was expressed in Escherichia coli, induced neutralizing antibodies in the fish Epinephelus septemfasciatus and Chromileptes altivelis, and induced protection against challenge by RGNNV genotype viruses (Tanaka et al 2001, Yuasa et al 2002. A similar vaccine efficacy was obtained in juvenile turbot Scophthalmus maximus by intraperitoneal injection of an oil-emulsified recombinant coat protein from SJNNV (Húsgard et al 2001). The present immunization of kelp grouper with recombinant coat proteins demonstrated that anti-RGNNV and anti-BFNNV had cross-neutralizing activity against the heterologous RGNNV and BFNNV, but anti-SJNNV serum and anti-TPNNV serum neutralized only homologous virus (Table 5).…”
mentioning
confidence: 67%
“…Intramuscular injection of the recombinant RGNNV coat protein, which was expressed in Escherichia coli, induced neutralizing antibodies in the fish Epinephelus septemfasciatus and Chromileptes altivelis, and induced protection against challenge by RGNNV genotype viruses (Tanaka et al 2001, Yuasa et al 2002. A similar vaccine efficacy was obtained in juvenile turbot Scophthalmus maximus by intraperitoneal injection of an oil-emulsified recombinant coat protein from SJNNV (Húsgard et al 2001). The present immunization of kelp grouper with recombinant coat proteins demonstrated that anti-RGNNV and anti-BFNNV had cross-neutralizing activity against the heterologous RGNNV and BFNNV, but anti-SJNNV serum and anti-TPNNV serum neutralized only homologous virus (Table 5).…”
mentioning
confidence: 67%
“…To ensure that the fish are as healthy as possible, a useful and practical approach would be vaccination of fish and boosting their immune system. Various types of vaccines have been developed such as formalininactivated vaccine, subunit vaccine with recombinant coat protein of betanodavirus and nodavirus-like particle vaccine [58,74,111,116,118,121,124]. Vaccination trials have shown protection efficacy against betanodavirus infection.…”
Section: Disease Control Strategiesmentioning
confidence: 99%
“…Vaccination trials have shown protection efficacy against betanodavirus infection. For example, recombinant partial capsid protein of SJNNV [58] and AHNV [111] vaccinated turbot and Atlantic halibut fish are protected significantly against nodavirus challenge. Additionally, use of DNA vaccine based on the gene encoding for G protein of VHSV offers high but short term protection against the nodavirus infection [109].…”
Section: Disease Control Strategiesmentioning
confidence: 99%
“…The outbreak in Norway coincides with a decline in halibut fry production, and is probably the most important reason why Norway's production of halibut fry has been level since 1995. No vaccine is currently available, although the development of a vaccine has been initiated using the turbot Scophthalmus maximus as an animal model (Húsgar7 et al 2001). Outbreaks of VER in halibut, however, 61 Dis Aquat Org 48: [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] 2001 tend to occur at relatively early ontogenetic stages and before vaccination would be possible.…”
mentioning
confidence: 99%